THE CASTLE, THE TOWN OF RASHAN (TREPÇA) - Hajzeri, Pajazit (European Scientific Journal, ESJ, 2014)
During the long history of the Albanian people, an almost forgotten part, and without being sufficiently studied, is the cultural heritage with special emphasis on fortified buildings as is the town (alb. “Gjyteti”) of Rashan (Trepça). The paper about Trepça castle is the first paper that addresses the current condition of the castle and brings historical data, oral legends that are still part of the memory of population, toponyms, microtoponyms, and also assumptions regarding the history of this castle with extraordinary historic values about the past of the Albanian people in this area. The uniqueness of this castle is its role in protecting the mining and mineral wealth of Bajgora region, and the main roads that gravitated to this part of Kosova. Another novelty is the drawing of the castle’s layout which is presented for the first time, and a number of photographs that reflect the current condition of the castle. This paper will serve as a guide for knowing this castle, and also for eventual intervention to conserve and restore the castle in order to return its treasured historic values as a symbol of the past. It is interesting the case of some holes found west to the castle’s surrounding wall, 0.9 cm deep, and with a diameter of 0.6 cm, that looked like they were there to drain the water, but their construction, I think, was an architectonic work that reinforced the wall in case of a tectonic quake (earthquake).